Faktor-Faktor yang Mempengaruhi Hasil Belajar Atletik Pada Mahasiswa Porkes UNJA Angkatan 2024 - Aldi Ramadhan; Boy Indrayana; Mhd Usni Zamzami Hasibuan (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Environmental changes and the development of science and technology demand improvements in the quality of education, including the achievement of students’ academic performance. As the young intellectual generation, university students play a vital role in shaping the nation's future; therefore, the factors influencing learning outcomes need to be examined. This study aims to analyze the factors affecting athletic learning outcomes among students of the Physical Education and Health Study Program (Porkes) at Jambi University, class of 2024.The research employs a quantitative approach with a descriptive method through surveys and data collection using questionnaires. The study sample consisted of 35 randomly selected students from a total population of 170. The results indicate that physical condition factors (69%), psychological factors (65%), environmental factors (66%), lecturer-student interaction (67%), as well as facilities and infrastructure (70%) fall into the high category in influencing athletic learning outcomes. Overall, these factors contribute 67% to the learning outcomes, indicating a significant impact. The implication of this study is the importance of paying attention to physical, psychological, learning environment, educational interaction, and supporting facilities aspects in order to enhance students’ academic achievement.